GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE IN MARIGOLD HYBRIDS ( IN MARIGOLD HYBRIDS (Tagetes agetes spp.) - AND V. S. PATIL, V. P. DEEPA (The Bioscan, 2018)
Genetic variability, heritabality and genetic advance studies showed high range for number of flower per plant (19.57-44.10) and fresh weight of flower (2.94-16.89 g). The co-efficient of variation (PCV and GCV) was maximum for number of flower per plant (PCV=50.33, GCV=52.56) and minimum for diameter of flower (PCV=17.21, GCV=16.90). The highest value of heritability was obtained for fresh weight of leaves (100.0), number of flower per plant (100.0), fresh weight of flower (99.0) and flower yield ton per hectare (99.0). High heritability with low genetic gain was observed for diameter of flower (h2 =96.0, GA=2.31), peduncle length (h2 =97.0, GA=2.23), fresh weight of flower (h2 =99.0, GA=8.51) and dry weight of flower (h 2 = 94.0, GA=0.71). As the high heritability and genetic advance as percent mean are due to additive type of gene action selection will be effective for all the characters in both crosses.